Pengaruh perbedaan level pupuk urin terfermentasi pada media tanam hidroponik terhadap komposisi dan kecernaan nutrien fodder sorgum - Harwanto Harwanto; Eko Hendarto; Bahrun Bahrun; Joni Johanda Putra; Nur Hidayat (Livestock and Animal Research, 2021)
Objective: This study aims to determine the nutritional value and nutrient digestibility by in vitro of fodder sorghum (Sorghum bicolor (L.) Moench) from the effect of the addition of fermented urine fertilizer to the hydroponic media.Methods: The research used sorghum Numbu varieties grown hydroponically in the fodder phase, which was carried out in June - September 2020. The research treatments consist of water medium (T1), fermented urine 12.5 mL/L (T2) and 25 mL/L media (T3) with 4 replications. The urine fertilizer used was derived from fermented Ongole Crossbreed cow urine for 21 days. Fodder sorghum planted for 15 days. The results of the fodder harvest were analyzed by proximate and in vitro nutrient digestibility. Observation nutritional value parameters consists of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), crude fiber (CF), total nutrient digestible (TDN), dry matter digestibility (DMD) and organic matter digestibility (OMD). Data were analyzed using one way ANOVA design, the significance by Duncan's Multiple Range Test.Results: The results showed that the addition of fermented urine had no effect on the DM, OM, and EE, but had a significant effect (P <0.05) on CP, CF, TDN and nutrient digestibility. The T2 and T3 treatments increased crude protein by 6.31% and 11.23% compared to T1. T3 treatment increased organic matter digestibility by 3.06% compared to T1.Conclusions: It can be concluded that the crude protein and organic matter digestibility of sorghum fodder at 15 days harvest stage, increases with the addition of fermented cattle urine up to 25.0 ml/L hydroponic media.